Effects of socioeconomic status on patient-reported outcome after surgically treated trigger finger: a retrospective national registry-based study - Malin Zimmerman; Mattias Rydberg; Lars B Dahlin; Lovisa Lesand (BMJ Open)
Objectives To investigate if socioeconomic status impacts patient-reported outcomes after a surgically treated trigger finger (TF).Design and setting Data on patients with TF treated with surgery were collected from the Swedish National Quality Registry of Hand Surgery (HAKIR) 2010–2019 with an evaluation of symptoms and disability before surgery and at 3 and 12 months after surgery, using the short version of the Disabilities of Arm, Shoulder and Hand (QuickDASH) questionnaire.Data from HAKIR and the Swedish National Diabetes Registry (ndr.nu) were combined with socioeconomic data from Statistics Sweden (scb.sc), analysing the impact of marital status, education level, income, occupation, sickness benefits, days of unemployment, social assistance and migrant status on the outcome by a linear regression model.Participants In total, 5477 patients were operated on for primary TF during the study period, of whom 21% had diabetes, with a response rate of 35% preoperatively, 26% at 3 months and 25% at 12 months.Results At all time points, being born in Sweden (preoperatively B-coefficient: −9.74 (95% CI −13.38 to −6.11), 3 months postoperatively −9.80 (95% CI −13.82 to −5.78) and 12 months postoperatively −8.28 (95% CI −12.51 to −4.05); all p<0.001) and high earnings (preoperatively −7.81 (95% CI −11.50 to −4.12), 3 months postoperatively −9.35 (95% CI −13.30 to −5.40) and 12 months postoperatively −10.25 (95% CI −14.37 to −6.13); all p<0.0001) predicted lower QuickDASH scores (ie, fewer symptoms and disability) in the linear regression models. More sick leave during the surgery year predicted higher QuickDASH scores (preoperatively 5.77 (95% CI 3.28 to 8.25; p<0.001), 3 months postoperatively 4.40 (95% CI 1.59 to 7.22; p<0.001) and 12 months postoperatively 4.38 (95% CI 1.35 to 7.40; p=0.005)). No socioeconomic factors impacted the change in QuickDASH score from preoperative to 12 months postoperatively in the fully adjusted model.Conclusion Individuals with low earnings, high sick leave the same year as the surgery and those born outside of Sweden reported more symptoms both before and after surgery, but the relative improvement was not affected by socioeconomic factors.